2021
DOI: 10.1111/bph.15393
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of atorvastatin on sex‐specific cognitive impairment induced by a cerebral microhaemorrhage in mice

Abstract: Background and Purposes: Cerebral microhaemorrhages (CMHs) are associated with cognitive decline in humans. In rodents, CMHs induces cognitive impairment in male mice along with sex-specific cortical and hippocampal changes affecting neural, glial and vascular functions. Statins, have been proposed to prevent cognitive decline. We tested here the action of atorvastatin on CMH-induced cognitive impairment in a murine model of CMH. Experimental Approach: Using a multimodal approach combining behavioural tests, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Indeed, we found just one trial matching these premises (Table 3) (Zissimopoulos et al, 2017). A recent preclinical study investigated the possible neuroprotective action of atorvastatin after the induction of cerebral microhemorrhages (Bergeron et al, 2021). Strikingly, authors found that atorvastatin improved visuospatial memory in males but not in females.…”
Section: Neurological Effects Of Lipid‐reducing Therapies and Sex Dif...mentioning
confidence: 99%
“…Indeed, we found just one trial matching these premises (Table 3) (Zissimopoulos et al, 2017). A recent preclinical study investigated the possible neuroprotective action of atorvastatin after the induction of cerebral microhemorrhages (Bergeron et al, 2021). Strikingly, authors found that atorvastatin improved visuospatial memory in males but not in females.…”
Section: Neurological Effects Of Lipid‐reducing Therapies and Sex Dif...mentioning
confidence: 99%